Complete atrio-ventricular block - Lourenço, António (2000)
The authors described a patient with arterial hypertension and complete heart block, diagnosed by the family physician; a few days after permanent pacemaker implantation on a pacing unit, the patient developed a complication and went again to his family doctor.